Glioblastoma, IDH-Wild Type With FGFR3-TACC3 Fusion: When Morphology May Reliably Predict the Molecular Profile of a Tumor. A Case Report and Literature Review - Broggi, Giuseppe; Piombino, Eliana; Altieri, Roberto; Romano, Chiara; Certo, Francesco; Barbagallo, Giuseppe Maria Vincenzo; Vigneri, Paolo; Condorelli, Dario; Colarossi, Lorenzo; Colarossi, Cristina; Magro, Gaetano; Tirrò, Elena (Frontiers in Neurology, 2022)
It has been reported that in-frame FGFR3-TACC3 fusions confer to glioblastomas, IDH-wild type (GBMs, IDHwt) some unusual morphologic features, including monomorphous rounded cells with ovoid nuclei, nuclear palisading, endocrinoid network of “chicken-wire” vessels, microcalcifications and desmoplastic stroma, whose observation may predict the molecular profile of the tumor. We herein present a case of recurrent GBMs, IDHwt, exhibiting some of the above-mentioned morphological features and a molecularly-proven FGFR3-TACC3 fusion. A 56-year-old man presented to our hospital for a recurrent GBM, IDHwt, surgically treated at another center. Histologically, the tumor, in addition to the conventional GBM morphology, exhibited the following peculiar morphologic features: (1) monomorphous neoplastic cells with rounded nuclei and scant pale cytoplasm; (2) thin capillary-like vessels with “chicken-wire” pattern; (3) nuclear palisading; (4) formation of vague perivascular pseudorosettes; (5) spindled tumor cells embedded in a loose, myxoid background. Based on this unusual morphology, molecular analyses were performed and an FGFR3 exon17-TACC3 exon 10 fusion was found. The present case contributes to widening the morphologic spectrum of FGFR3-TACC3-fused GBM, IDHwt and emphasizes that pathologists, in the presence of a GBM, IDHwt with unconventional morphology, should promptly search for this fusion gene.